Correlation between ankle stiffness and antagonist co-activation in post-stroke subjects. (17th February 2020) - Ribeiro, Edgar; Silva, Augusta; Pinho, Liliana; Santos, Rubim; Pinho, Francisco; Sousa, Andreia S.P.
Tonus dysfunction has been broadly investigated in post-stroke subjects through the evaluation of muscle resistance against stretching, however, its characterisation in functional context is challenging. This study aims to analyse the correlation between intrinsic stiffness, functional stiffness and antagonist co-activation at the ankle joint of post-stroke subjects. Both lower limbs of eight post-stroke participants were evaluated. Intrinsic stiffness was assessed during passive dorsiflexion by an isokinetic dynamometer, functional stiffness during upright standing on a force platform and antagonist co-activation was obtained in upright standing and postural phases of gait initiation and stand-to-sit through the electromyographic signal of ankle muscles. A significant positive correlation was found between antagonist co-activation of ipsilesional tibialis anterior/soleus pair in upright standing and functional stiffness ( r = 0.810; p = 0.015; 1- &#946 ; = 0.899). Antagonist co-activation seems to be related to functional stiffness in upright standing, suggesting the relevance of evaluating tonus dysfunction through motor control variables obtained under functional conditions.